Pencil yourself a humidity-driven continuous roll Paperbot - Ainizar, Mustapa; Abu Hannifa, Abdullah; Wan Farhana, W. Idris; Zulhelmi, Ismail (Elsevier Ltd, 2025)
Developing a continuous actuator material that changes in environmental conditions that can power up would benefit various future electronics, robotics, or medical sectors as it could be wireless, and mobile while remaining lightweight. However, the process involved in preparing the materials for the actuator may not often be accessible to many due to the difficult procedure for assembly or utilization of specialized chemicals for actuator active materials. In this work, we reported a facile approach to fabricate an origami paper-based actuator named Paperbot that may mechanically be driven by the presence of surrounding humidity ( 60 %RH) and is able to continuously roll at the working temperature of up to 95 °C with a 99 %RH moisture level. The millipede-inspired bot consists of a head, body, and tail, while it is assembled using a cellulose paper as the body matrix, with graphite pencil and bi-axially oriented polypropylene tape acting as the active and support material, on both head and tail, respectively. Upon activation by humidity vapor, the actuator flips and rolls up to 6.3 cm with a linear speed of 8 mm/s, is able to climb up and down a 63° inclined terrain, and can further be programmed into 4-unique projectile motions after different shape geometries patterning on the actuator body. A combination of origami and pattern-based actuators in this work, while perhaps simple, could provide an in-depth understanding of the operation of a humidity-driven paper-based continuous actuator for the future.